Wacana Keadilan Shahabat Dalam Pandangan Ulama Klasik Dan Kontemporer - Nafisah, Lailiyatun; Muhtador, Mohammad (AL QUDS : Jurnal Studi Alquran dan Hadis, 2018)
The writing explains the discourse of classical and contemporary scholars regarding friend justice, as something urgent in the narration of hadith. Argumentatively-dogmative this paper constructs the justice of friends in the classical ulama perspective, as well as the argumentative-dogmatic of contemporary scholars regarding friend justice in the narrative of the hadith as a comparison. This study is literary in nature which refers to qualitative methods that collect data from various Islamic literature that are considered to have relevance. So that it can be concluded that the religious scholars of the past had a friend's belief that they were just people guaranteed by the Prophet as human beings in their time, the Sunni argument was contradicted by contemporary scholars